(untitled) (Clinics, 2009)
OBJECTIVE: The aim of this study was to evaluate the effects of isoflavones on the skin of postmenopausal women. DESIGN: A prospective study was performed with 30 postmenopausal women before and immediately after the end of treatment with 100 mg/day of an isoflavones-rich, concentrated soy extract for six months. A skin punch was performed in the gluteal region for sample collection before and immediately after the treatment program. Morphometric determination of epidermal thickness, the papillary index (wrinkling), and the amount of dermal elastic and collagen fibers was assessed. In addition, the number of blood vessels in the sample was also evaluated. The paired Student's t-test was used for statistical analysis (P < 0.05). RESULTS: Isoflavone treatment resulted in a 9.46% increase in the thickness of the epidermis in 23 patients. In addition, the papillary index was reduced in 21 women. The papillary index was inversely proportional to skin wrinkling, i.e., there were a large number of papillae after treatment. The amount of collagen in the dermis was increased in 25 women (86.2%). In 22 women (75.8%) we observed that the number of elastic fibers increased. The number of dermal blood vessels was significantly increased in 21 women. CONCLUSION: Our data show that the use of a concentrated, isoflavone-rich soy extract during six consecutive months caused significant increases in epithelial thickness, the number of elastic and collagen fibers, as well as the blood vessels.